The quantitative and qualitative evolution of the social security research - Ruiz Estrada, Mario Arturo; Koutronas, Evangelos (Springer Verlag, 2018)
This article examines the evolution of social security research from a theoretical and empirical perspective. This is done through an extensive review and analysis of publications from the Journal of International Social Security Review published by Wiley within a 50-year period (1967–2017). It was observed that at a different period in time, the social security research focused on different national and international issues that invoked different social welfare programs and pension systems approach (public or private) to facilitate the explanation of its final socio-economic impact into different social groups in the same country or region respectively.